Folate Deficiency in Chronic Pancreatitis - Rajesh, Gopalakrishna; Girish, Banavara Narasimhamurthy; Vaidyanathan, Kannan; Saumya, Menon; Balakrishnan, Vallath (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Logo of "Amrita Institute of Medical Sciences". Cochin, Kerala, India